INVENTARISASI MEDIA PUBLIKASI PERIKANAN PADA INSTANSI DI LINGKUNGAN PEMERINTAH PROVINSI RIAU - Tita Yuniasih; Ridar Hendri; Kusai ' (Berkala Perikanan Terubuk, 2014)
ABSTRACTThis aims of this studied to inventory the fisheries publication media issued by the procvincial government agencies during 2013. Data collection used the studied of documentation on fisheries publication media. The study was conducted on September to Oktober 2013 at the 10 agencies that published media containing fisheries information.The result showed, the types of fisheries publication media issued by agencies in Riau Provincial Government amounted to 16 types namely; newspapers, magazines, tabloids, books, booklets, leaflets folders, buletins, journals, advocacy media, posters, calendars, billboards, video, online media, and television shows.The amount of publication of fisheries information publized by agencies in Riau Provincial Government on 2013 was 621.289.560cm2. Media provides the most space for publishing fisheries information was newspapers352.102.059 cm2 (56,67%) and the least was television show 182.700 cm2 (0,03%). The types of fisheries information that most widely publicized were fisheries socioeconomic (41,12%), aquculture (24,35%), aquatic product technology (24,05%), fisheries resource management (4,55%), aqutic product management (3,36%), and marine (2,55%).Keywords: Media Publication, Fisheries Information, Agencies